2018
DOI: 10.1097/md.0000000000011120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of led photobiomodulation on analgesia during labor

Abstract: Background:Labor pain is one of the most intense pains experienced by women, which leads to an increase in the number of women opting to undergo a cesarean delivery. Pharmacological and nonpharmacological analgesia methods are used to control labor pain. Epidural analgesia is the most commonly used pharmacological analgesia method. However, it may have side effects on the fetus and the mother. Light-emitting diode (LED) photobiomodulation is an effective and noninvasive alternative to pharmacological methods.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…So far, PBM has been applied to treat several human diseases such as stroke, Parkinson's disease, Alzheimer's disease, traumatic brain injury, and psychiatric disorders [115]. Although there have been some studies relevant to light therapy [116,117] in pregnancy, none of them have focused on offspring outcomes in adulthood. In the area of complementary and alternative medicine, several suggested therapies for insomnia might be applied for treating chronodisruption, despite not yet being recommended as standard therapies [118].…”
Section: Light and Circadian Signaling-related Therapy In Human Diseasesmentioning
confidence: 99%
“…So far, PBM has been applied to treat several human diseases such as stroke, Parkinson's disease, Alzheimer's disease, traumatic brain injury, and psychiatric disorders [115]. Although there have been some studies relevant to light therapy [116,117] in pregnancy, none of them have focused on offspring outcomes in adulthood. In the area of complementary and alternative medicine, several suggested therapies for insomnia might be applied for treating chronodisruption, despite not yet being recommended as standard therapies [118].…”
Section: Light and Circadian Signaling-related Therapy In Human Diseasesmentioning
confidence: 99%
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the effect of LED on analgesia during labor, the following variables were assessed: (1) perception of pain, (2) fetal well-being assessed by cardiotocography or intermittent auscultation, (3) Apgar score at minutes 1 and 5 after birth, and (4) labor duration. 15 Pain perception was assessed by means of the visual analog scale (VAS) with scores and a continuous ruler varying from 0 to 10, before and after the intervention. The scale had a size of 10 cm, and patients were given an explanation that 10 meant the strongest pain they had ever felt and 0 meant absence of pain, and then they would point to a number on the scale that corresponded to the pain they were feeling at the time.…”
Section: Methodsmentioning
confidence: 99%